2012 Olympics: who will survive? - Hamlyn, P. J.; Hudson, Z. L. (British Journal of Sports Medicine, 2005)
Five cities were in pursuit of the 2012 Olympics. At the heart of each application was the bid document, which has crucial chapters on health and the Game`s legacy. The Evaluation Committee of the International Olympic Committee (IOC) visited each city and interrogated their medical advisors, one of the current authors included, on every detail of the proposed health provisions.